Globalization, poverty and social violence in Latin America - Chávez de Paz, Dennis (2007)
In the last decade, Latin America has been strengthened in its economic growth by the world process of globalization. However, this process has not had a significant impact on poverty reduction. The author examines the effects of globalization on these societies and shows that there is no real change in the productive conditions, since they continue to be mainly producers of raw materials with an extremely unequal distribution of wealth.